2022
DOI: 10.25071/1920-7336.40935
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Male Sexual Minority Asylum Seekers and Refugees in Nairobi, Kenya: A Aualitative Assessment

Abstract: Very little information exists about the experiences of asylum seekers and refugees who are men who have sex with men (MSM). Therefore, this study explores the psychological distress of MSM asylum seekers and refugees in the Nairobi metropolitan area. We collected data using in-depth interviews transcribed verbatim, coded using NVivo 12 Plus, and analyzed using the six-step thematic analysis framework. Four major themes emerged from the study: psychological distress, traumatic stress symptoms, mental health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…For example, 40% of respondents in a survey of 608 MSM in Kampala reported experiencing violence because of their same-sex behavior [13]. The findings were consistent with our study, which also found evidence of heightened mental distress caused by immigration stressors and post-traumatic experiences that continued to adversely affect the mental health of gay and bisexual asylum seekers and refugees in Nairobi [14]. However, there is limited evidence of the persecution experiences and the impact on the physical health of gay and bisexual asylees and refugees in Kenya.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, 40% of respondents in a survey of 608 MSM in Kampala reported experiencing violence because of their same-sex behavior [13]. The findings were consistent with our study, which also found evidence of heightened mental distress caused by immigration stressors and post-traumatic experiences that continued to adversely affect the mental health of gay and bisexual asylum seekers and refugees in Nairobi [14]. However, there is limited evidence of the persecution experiences and the impact on the physical health of gay and bisexual asylees and refugees in Kenya.…”
Section: Introductionsupporting
confidence: 89%
“…This analysis was part of our broader qualitative study conducted in 2020. The study assessed the intersectional identities, persecution experiences, and health needs of sexually minoritized asylum seekers and refugees in Nairobi, Kenya [16].…”
Section: Methodsmentioning
confidence: 99%